24 hour ambulatory oesophageal pH monitoring in uncomplicated Barrett's oesophagus. - Neumann, C S (1994)
The aim of this study was to compare acid reflux in 16 patients with uncomplicated Barrett's oesophagus with 37 patients with reflux oesophagitis and 10 control subjects of comparable age. All patients had 24 hour ambulatory pH monitoring within one week of endoscopy. The controls differed significantly from the other groups in all indices of reflux but there was no difference between the Barrett's oesophagus patients and the reflux oesophagitis patients in any index of reflux over the total 24 hour period. Barrett's oesophagus patients differed significantly, however, with respect to the percentage time pH < 4 and the number of reflux episodes of > five minutes during the supine period when compared with patients with grade I reflux oesophagitis, but not when compared with patients with grade II and III reflux oesophagitis. Barrett's oesophagus patients with associated grade II reflux oesophagitis had more reflux than those with no oesophagitis or grade I reflux oesophagitis. Within each disease group patients > or = 50 years had more acid reflux than patients < 50 years. The severity of acid reflux in patients with uncomplicated Barrett's oesophagus was no greater than in patients with reflux oesophagitis of comparable age. It seems probable that other factors must be important in the development of Barrett's oesophagus.